Rice Bran as Opportunity Media for Candida albicans Increase - Diah Titik Mutiarawati (Health Notions, 2021)
The incidence of invasive fungal infections caused by fungi of the genus Candida is reported to be increasing in various countries. C. albicans can be isolated and cultured in liquid media, one of which is PDB (Potato Dextrose Broth), a common medium used for the growth of yeasts and moulds. Bekatul or rice bran is a waste from rice milling, which still contains nutrients such as carbohydrates and protein, which are needed as energy sources for mushroom growth. Colonies were C. albicans grown in bran liquid media at mass concentrations of 20 grams, 40 grams, 60 grams, 80 grams and 100 grams with PDB as the gold standard. The colonies C. albicans growing were then confirmed by planting on PDA media (Potato Dextrose Agar), and microscopic testing was performed. The results showed that C. albicans grew well in bran liquid medium at pH 5.5-5.0, which was incubated for 1-5 days at a temperature of 25°C-30°C and was characterized by the growth of white colonies on the bottom of the tube, while the number of C. albicans that grew on liquid bran media was more than that of PDB media. The conclusion of this research is that the liquid bran media can be used as an alternative medium for PDB for the growth of the fungus C. albicans.Keywords: white rice bran; Candida albicans; alternative media; potato dextrose broth